Implementation of Multicultural Education in History Learning Loaded with Controversial History Materials at SMA Negeri 5 Semarang - Kartikasari, Meilatia; Utomo, Cahyo Budi; Amin, Syaiful (Universitas Negeri Semarang, 2016)
The purpose of this research is (1) to describe the content of multicultural education on controversial historical material. 2) to explain the implementation of multicultural education on controversial history content material by teachers of history subjects, (3) to describe response toward the implementation of multicultural education on history subjects with controversial issues. This research uses a qualitative method with a phenomenology approach at SMA Negeri 5 Semarang. Informants in this study were teachers, the waka curriculum, and students from the school. In this research, the data collection technique is observation, interview, and documentation. The analysis and presentation of data used are structured and specific analysis—the technique of examination of data validity using triangulation technique and source. The results showed that the learning planning made by the history teacher in SMA Negeri 5 Semarang has included multicultural education, although the curriculum has not been written explicitly. Most Students and teachers already understand the importance of multicultural education and its relation to the subject of contested historical material controversy.